2009
DOI: 10.1080/01676830802675877
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of a Case of Solitary Fibrous Tumor of the Orbit

Abstract: Solitary fibrous tumor of the orbit should be considered in the differential diagnosis of arterious hemangioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“…Precontrast MR imaging findings and an enhancement pattern of SFT in the orbit are so similar to those of schwannoma, however, that orbital SFT is often misdiagnosed as schwannoma preoperatively. 8,9 Our results suggested that the type of TIC on DCE MR imaging and the enhancement pattern of very high-signal-intensity areas shown on T2-weighted imaging might be useful in the differentiation between SFT and schwannoma in the orbit.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Precontrast MR imaging findings and an enhancement pattern of SFT in the orbit are so similar to those of schwannoma, however, that orbital SFT is often misdiagnosed as schwannoma preoperatively. 8,9 Our results suggested that the type of TIC on DCE MR imaging and the enhancement pattern of very high-signal-intensity areas shown on T2-weighted imaging might be useful in the differentiation between SFT and schwannoma in the orbit.…”
Section: Discussionmentioning
confidence: 92%
“…It had been reported that the higher T2 signal intensity areas in schwannoma are related to thrombosis of degenerating blood vessels, hemorrhage, hyaline degeneration, and/or microcystic foci in Antoni B pattern, which could explain the lack of enhancement of these areas. 9 The markedly enhanced very high T2 signal-intensity areas in orbital SFT might be related to areas of various cellular components rather than to the cystic or necrotic foci seen in schwannoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, precontrast MRI findings and an enhancement pattern of solitary fibrous tumor in the orbit may resemble those of schwannoma. 18 …”
Section: Discussionmentioning
confidence: 99%
“…These mesenchymal neoplasms are extremely rare in childhood. We found only 9 tumors classified as HPC 9-17 and 2, as STF 18,19 in patients younger than 10 years. They usually have a benign course, even though those that have cytologic atypia, necrosis, and 4 or more mitotic figures per 10 high-power fields can be locally aggressive or metastasize.…”
Section: Discussionmentioning
confidence: 94%